Model-theoretic optimization approach to triathlon performance under comparative static conditions - Results based on the Olympic Games 2012 - Fröhlich, M.; Balter, J.; Pieter, A.; Schwarz, M.; Emrich, E. (International Journal of Kinesiology & Sports Science, 2013)
In Olympic-distance triathlon, time minimization is the goal in all three disciplines and the two transitions. Running is the key to winning, whereas swimming and cycling performance are less significantly associated with overall competition time. A comparative static simulation calculation based on the individual times of each discipline was done. Furthermore, the share of the discipline in the total time proved that increasing the scope of running training results in an additional performance development. Looking at the current development in triathlon and taking the Olympic Games in London 2012 as an initial basis for model-theoretic simulations of performance development, the first fact that attracts attention is that running becomes more and more the crucial variable in terms of winning a triathlon. Run times below 29:00 minutes in Olympic-distance triathlon will be decisive for winning. Currently, cycle training time is definitely overrepresented. The share of swimming is considered optimal.